Resistance : Subjects, Representations, Contexts - Martin Butler; Paul Mecheril; Lea Brenningmeyer (transcript, 2017)
All around the world and throughout history, resistance has played an important role – and it still does. Some strive to raise it to cause change. Some dare not to speak of it. Some try to smother it to keep a status quo.The contributions to this volume explore phenomena of resistance in a range of historical and contemporary environments. In so doing, they not only contribute to shaping a comparative view on subjects, representations, and contexts of resistance, but also open up a theoretical dialogue on terms and concepts of resistance both in and across different disciplines.With contributions by Micha Brumlik, Peter McLaren, and others.